2022
DOI: 10.3389/fonc.2022.887257
|View full text |Cite
|
Sign up to set email alerts
|

Elevated BCAA Suppresses the Development and Metastasis of Breast Cancer

Abstract: Branched-chain amino acids (BCAAs) are the three essential amino acids including leucine, isoleucine, and valine. BCAA metabolism has been linked with the development of a variety of tumors. However, the impact of dietary BCAA intake on breast tumor progression and metastasis remains to be fully explored. Here, we unexpectedly find that the elevated BCAA, either in the genetic model or via increasing dietary intake in mice, suppresses the tumor growth and lung metastasis of breast cancer. The survival analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Dysregulation of the metabolism of branched-chain amino acids (BCAAs) including leucine (Leu), valine (Val), and isoleucine (Ile) has been reported to be associated with specific cancer phenotypes. BCAAs can inhibit the growth and metastasis of tumor [ 31 ], thereby changes in the content of BCAAs can often reflect the systemic changes in cancer patients compared to healthy controls [ 32 ]. Jasbi et al.…”
Section: Resultsmentioning
confidence: 99%
“…Dysregulation of the metabolism of branched-chain amino acids (BCAAs) including leucine (Leu), valine (Val), and isoleucine (Ile) has been reported to be associated with specific cancer phenotypes. BCAAs can inhibit the growth and metastasis of tumor [ 31 ], thereby changes in the content of BCAAs can often reflect the systemic changes in cancer patients compared to healthy controls [ 32 ]. Jasbi et al.…”
Section: Resultsmentioning
confidence: 99%
“…Another study postulated suppression of VEGF expression in tumour cells as an alternative mechanism[ 73 ]. The catabolism of BCAAs has also been extensively implicated in carcinogenesis[ 67 ] through various molecular pathways, including accumulation of branched-chain α-ketoacids and activation of the mTORC1 pathway[ 74 , 75 ]. Ericksen et al [ 76 ] validated oncogenic pathways and linked high dietary BCAA intake to tumour burden and mortality specifically in HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that in breast cancer mouse models, less lung metastases were observed in the high BCAAs diet-fed mice. The mechanism is that high levels of BCAAs activated tumor-infiltrating NK cells in lung metastases ( 124 ). This study indicates that high BCAA may not promote the proliferation of cancer cells in lung metastases, but conversely inhibit lung metastasis by promoting the activity of tumor-infiltrating NK cells in lung metastases ( Figure 4 ).…”
Section: Branched Chain Amino Acids Metabolismmentioning
confidence: 99%